Electro-optic characteristics of fringe-field-switching mode with controllable anchoring strength of liquid crystal alignment. (16th October 2015) - Lin, T-C; Chang, K-H; Song, Y; Hsieh, C; Lo, C-C; Lee, C; Alan Lien, S-C; Hasebe, H; Takatsu, H; Chien, L-C
Abstract: A photoalignment technique used in preparation of fringe-field-switching (FFS) mode cells is presented. The azimuthal anchoring energy (AAE) of photoalignment is controllable by tuning the UV exposure and if the value of AAE is as strong as that of the rubbing method. The electro-optical properties of FFS cells are optimized with different electrode configurations and high quality dark states of various types of cells are achieved to create the high contrast ratio. The great thermal stability shown after applying voltage and heat confirms that photoalignment is suitable for FFS mode applications.